Coming of age: health-care challenges of an ageing population in Israel. Issue 10088 (24th June 2017) - Dwolatzky, Tzvi; Brodsky, Jenny; Azaiza, Faisal; Clarfield, A Mark; Jacobs, Jeremy M; Litwin, Howard
Summary: Although Israel is still young in years, with relatively high birth rates and older people (individuals aged 65 years or older) constituting only about 11% of its population, the absolute number of older people is growing rapidly. Life expectancy is high, and increasing numbers of people are living to advanced old age (older than 85 years). A wide spectrum of geriatric care is provided within a universal system providing health services to all citizens. Community and institutional care is available, and many innovative programmes are being developed. The unique demographic characteristics of the ageing society in Israel reflect cultural and multiethnic diversity, in addition to a high rate of immigration of older people. To meet the growing challenges, address disparities, and search for innovation will require planning and development of adequate services at the highest level.